Implications of the Decision of the Regent of North Tapanuli Number 6 of 2022 on the Provision of Land Services to the Community - Freddi Agus Hutapea; Henry Aspan; Abdul Rahman Maulana Siregar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Challenges in establishing customary forests in Indonesia are caused by complicated bureaucracy, lack of synchronization between central and local bureaucracy, and the politics of citizen struggle using the identity of indigenous peoples. In the face of changes to Areal Penggunaan Lain (APL), there needs to be a careful approach and close collaboration between the local government, the central government, and indigenous peoples to achieve a balance between economic development, environmental preservation, and the rights of indigenous peoples. The research specification used in this research is descriptive analytical, which seeks to describe or describe events and events without conducting hypotheses and statistical calculations. Also normative juridical, namely research based on Ministerial regulations, books, and decrees of the Regent of North Tapanuli. The central and local governments have taken significant steps in recognizing and protecting the traditional and cultural rights of indigenous peoples. Changes in the Areal Penggunaan Lain (APL) can have serious impacts, requiring a cautious approach and close collaboration to maintain a balance between economic development, environmental preservation and the rights of indigenous peoples. Suggestions are made that local and central governments improve collaboration, concretely empower indigenous peoples, and integrate sustainable measures in policies to achieve a sustainable balance.